Liquid-phase epitaxial growth of two-dimensional semiconductor hetero-nanostructures - Tan, Chaoliang (2015)
Although many two-dimensional (2D) hybrid nanostructures are being prepared, the engineering of epitaxial 2D semiconductor hetero-nanostructures in the liquid phase still remains a challenge. The preparation of 2D semiconductor hetero-nanostructures by epitaxial growth of metal sulfide nanocrystals, including CuS, ZnS and Ni3S2, is achieved on ultrathin TiS2 nanosheets by a simple electrochemical approach by using the TiS2 crystal and metal foils. Ultrathin CuS nanoplates 50–120 nm in size and with a triangular/hexagonal shape are epitaxially grown on TiS2 nanosheets with perfect epitaxial alignment. ZnS and Ni3S2 nanoplates can be also epitaxially grown on TiS2 nanosheets. As a proof-of-concept application, the obtained 2D CuS–TiS2 composite is used as the anode in a lithium ion battery, which exhibits a high capacity and excellent cycling stability.